2010
DOI: 10.1590/s0102-05362010000100019
|View full text |Cite
|
Sign up to set email alerts
|

Reação de genótipos de tomateiro às raças 2 e 3 de Fusarium oxysporum f. sp. lycopersici

Abstract: Reaction of tomato genotypes to races 2 and 3 of Fusarium oxysporum f. sp. lycopersici

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…P = rootstocks; N = nematode; F = Fusarium; FC/IC = Final count/Initial count; EE = experimental error, CV = coefficient of variance. Even though the F1 plants were inoculated with F. solani, only 3 species presented signs of rootsystem infection, as reported by Souza et al (2010), while 2 species showed a higher resistance: S. asperolanatum with Fusarium and N. glauca with Fusarium. Among the susceptible species, S. auriculatum presented infection signs sooner than the tree tomato.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…P = rootstocks; N = nematode; F = Fusarium; FC/IC = Final count/Initial count; EE = experimental error, CV = coefficient of variance. Even though the F1 plants were inoculated with F. solani, only 3 species presented signs of rootsystem infection, as reported by Souza et al (2010), while 2 species showed a higher resistance: S. asperolanatum with Fusarium and N. glauca with Fusarium. Among the susceptible species, S. auriculatum presented infection signs sooner than the tree tomato.…”
Section: Resultssupporting
confidence: 58%
“…Tree tomato is a promising crop all over the world and it has been researched to increase its postharvest time (Pinzón-Gómez et al, 2014). Nonetheless, as a member of the Solanaceae family, its root system is affected by fungi of the Fusarium genus (Souza et al, 2010). In addition to this, one of the members of this genus (Fusarium solani) not only affects tree tomato rootneck, causing plants to rot, but also affects several other plants that are important to production (Benítez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Spore suspensions with a concentration of 1 × 10 6 conidia mL −1 were prepared from 7‐day‐old cultures (Cai et al., 2003). Tomato seedlings at 15 days of age were removed from the trays, had their root tips cut, and were immersed in the spore suspension for 5 min (Souza et al., 2010). The experimental design used was completely randomized, with six replicates for each isolate.…”
Section: Methodsmentioning
confidence: 99%
“…Symptom severity of the shoot system of the plants was assessed (6-weeks after pathogen inoculation) using the following index (Souza et al, 2010): 0: no symptoms, 1: yellowing 1 -25% of the leaves near the stem base, 2: Yellowing and wilt 26-50% of leaves with a simple brown discoloration in xylem vessels, 3: Yellowing and wilt 51 -75% of the leaves with dark brown coloring in xylem vessels, 4: Wilt and die 76-100% of leaves.…”
Section: Percentage Of Disease Severities and Infectionmentioning
confidence: 99%